Evaluation of image quality and assessability of a new flat‐panel 3D C‐arm compared to mobile and fixed computed tomography in posterior spinal fixation. Issue 2 (28th October 2020) - Keil, Holger; Luxenhofer, Miriam; Vetter, Sven Y.; Beisemann, Nils; Grützner, Paul A.; Franke, Jochen
Abstract: Background: This study evaluates image quality of a new flat‐panel three‐dimensional (3D) C‐arm to the current generation and to intraoperative and stationary computed tomography (CT) in spinal surgery. Methods: Three‐dimensional‐imaging of 44 posterior screws acquired with two generations of 3D C‐arms (Arcadis Orbic, AO and Cios Spin, CS, Siemens, Germany) and CT scans (mobile intraoperative CT Airo, iCT, Brainlab, Germany and stationary CT Aquilion 32, sCT, Toshiba, Japan) were performed. Evaluation regarded assessability and measurements of implant position. Results: Assessability score was 0.11 in AO, 0.56 in sCT, 0.91 in iCT and 1.46 in CS ( p < 0.0005). AO and CS showed a significant difference in accuracy ( p = 0.001) as well as CS and iCT ( p < 0.001). Measurements of protrusion over the anterior edge did not show a significant difference ( p = 0.341). Conclusions: Image quality of the new generation of flat‐panel 3D C‐arms competes with CT imaging and offers significant advantages compared to the former generation.